2017
DOI: 10.1002/art.40231
|View full text |Cite
|
Sign up to set email alerts
|

CD11b+Gr‐1dim Tolerogenic Dendritic Cell–Like Cells Are Expanded in Interstitial Lung Disease in SKG Mice

Abstract: We identified unique suppressive myeloid cells that were differentiated from monocytic MDSCs in SKG mice with ILD, and we termed them CD11b+Gr-1 tolerogenic DC-like cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…We recently reported that MDSCs are expanded in the lungs of SKG mice with interstitial lung disease (ILD) [ 27 ]. Other researchers demonstrated that CCR2 + M-MDSCs inhibit collagen degradation and promote lung fibrosis by producing transforming growth factor-β1 (TGF-β1) [ 28 ].…”
Section: Main Textmentioning
confidence: 99%
“…We recently reported that MDSCs are expanded in the lungs of SKG mice with interstitial lung disease (ILD) [ 27 ]. Other researchers demonstrated that CCR2 + M-MDSCs inhibit collagen degradation and promote lung fibrosis by producing transforming growth factor-β1 (TGF-β1) [ 28 ].…”
Section: Main Textmentioning
confidence: 99%
“…Interestingly, the highest expression protein pattern of Gr-1+/CD44+ (Gr-1+ bright /CD44+ bright ) within the CD11b+ subset was associated with early cancer disease in the blood of cisplatin treated 4T1 tumorous mice. The Gr-1+ dim /CD44+ dim immature myeloid cells have been reported to suppress T-cells and IFN-γ production [37,38], the dim expression intensity of these markers was characteristic to 4T1 tumor bearing mice (Figure 8). In line with this, the smaller population of IFN-γ producing myeloid cells appeared within the CD11 subtype by cisplatin treatment which was completely absent in the advanced cancer ( Figure 8).…”
Section: Cisplatin Could Not Completely Restore the Peripheral Immunomentioning
confidence: 95%
“…34,35 In this context, local lung epithelial DC function is suppressed by transforming growth factor-β (TGFβ), promoting immune tolerance, while others such as granulocyte macrophage colony stimulating factor (GM-CSF) promote DCmediated inflammation and autoimmunity. [35][36][37] Exactly how tobacco smoke may induce autoimmunity is not clear. It is composed of many chemicals, of which polycyclic aromatic hydrocarbons (PAHs) are known to activate the aryl hydrocarbon receptor, which is upregulated in RA synovial tissues.…”
Section: Pathobiology Of Rheumatoid Arthritis Lung Diseasementioning
confidence: 99%
“…38 Mice that are aryl hydrocarbon receptor deficient are resistant to collagen-induced arthritis and have attenuated Th17 immunity. 37 Peptidylarginine deiminase (PAD) enzymes regulate the conversion of peptidylarginine to peptidylcitrulline in a calcium-dependent reaction referred to as citrullination. PAD2 levels in the upper and lower airways are elevated in smokers, who also have higher levels of citrullinated peptides in BAL cells.…”
Section: Pathobiology Of Rheumatoid Arthritis Lung Diseasementioning
confidence: 99%